Highly Efficient Electrocatalytic Uranium Extraction from Seawater over an Amidoxime‐Functionalized In–N–C Catalyst. Issue 23 (17th June 2022) - Liu, Xiaolu; Xie, Yinghui; Hao, Mengjie; Chen, Zhongshan; Yang, Hui; Waterhouse, Geoffrey I. N.; Ma, Shengqian; Wang, Xiangke
Abstract: Seawater contains uranium at a concentration of ≈3.3 ppb, thus representing a rich and sustainable nuclear fuel source. Herein, an adsorption–electrocatalytic platform is developed for uranium extraction from seawater, comprising atomically dispersed indium anchored on hollow nitrogen‐doped carbon capsules functionalized with flexible amidoxime moieties (In–N x –C–R, where R denotes amidoxime groups). In–N x –C–R exhibits excellent uranyl capture properties, enabling a uranium removal rate of 6.35 mg g −1 in 24 h, representing one of the best uranium extractants reported to date. Importantly, In–N x –C–R demonstrates exceptional selectivity for uranium extraction relative to vanadium in seawater (8.75 times more selective for the former). X‐ray absorption spectroscopy (XAS) reveals that the amidoxime groups serve as uranyl chelating sites, thus allowing selective adsorption over other ions. XAS and in situ Raman results directly indicate that the absorbed uranyl can be electrocatalytically reduced to an unstable U(V) intermediate, then re‐oxidizes to U(VI) in the form of insoluble Na2 O(UO3 ·H2 O) x for collection, through reversible single electron transfer processes involving InN x sites. These results provide detailed mechanistic understanding of the uranium extraction process at a molecular level. This work provides a roadmap for the adsorption–electrocatalytic extraction of uranium from seawater, adding to the growing suite of technologies for harvesting valuable metals from the earth's oceans. Abstract : Porous indium−nitrogen−carbon capsules functionalized with flexible amidoxime groups enable highly efficient uranium extraction from seawater. The flexible amidoxime groups allow selective uranyl adsorption, while the InN x single atom sites provide a reversible single electron transfer platform for uranyl conversion to a harvestable Na2 O(UO3 ·H2 O) x precipitate via a U(V) intermediate.